Anaphylaxis: Turkish National Guideline 2018 - Orhan, Fazil; Civelek, Ersoy; Sahiner, Umit Murat; Arga, Mustafa; Can, Demet; Calikaner, Ahmet Zafer; Yilmaz, Ozge (Turkish Natl Soc Allergy and Clinical Immunology, 2018)
Anaphylaxis is an acute and potentially fatal systemic reaction that sould be recognized and managed by all helthcare professionals. This is the first national guideline of Turkish National Society of Allergy and Clinical Immunology on diagnosis and management of anaphylaxis. The guideline is prepared by Anaphylaxis Interest Group with the incorporation of 20 allergy/immunology specialists and the epidemiology, etiology, pathophysiology, symptoms and signs, diagnosis/differentials, and acute and long-term management of anaphylaxis are reviewed in detail.
Keywords: Anaphylaxis; National guideline; Turkish National Society of Allergy and Clinical Immunology